The Effect of Psychological Capital on Academic Success of College Students Mediated Through Student Engagement - Gebregergis, Werede Tareke; Kovács, Karolina Eszter; Csukonyi, Csilla (Central European Journal of Educational Research, 2024)
Although psychological capital is theorized to enhance academic success of college students, there is a lack of sufficient empirical evidence supporting this claim. Given this gap, the present study was conducted to explore the role of psychological capital in academic success of college students, mediated through student engagement. Undergraduate and postgraduate diploma students (N=502) were selected using a convenience sampling technique. The participants completed self-reported questionnaires assessing their psychological capital, student engagement, and academic success. To determine the statistical significance of the prediction, hierarchical multiple regression analyses were performed. PROCESS macro for SPSS was utilized for analyzing the mediation effect. Results obtained from the regression analyses revealed that psychological capital was positively and significantly related to both engagement and academic success. Notably, the mediation results also demonstrated that student engagement partially mediated the relationship between psychological capital and academic success. The results of the present study might contribute to the existing literature related to the importance of positive psychology in education by providing insight into the complicated relationship between psychological capital, student engagement, and academic success.